YIELD OF CORN IN AREA OF CROP X PASTURE INTEGRATION UNDER THE SYSTEM OF NO TILLAGE, IN PRESENCE AND ABSENCE OF WHITE CLOVER, GRAZING AND NITROGEN - ASSMANN, Tangriani Simioni (Scientia Agraria, 2002)
A field experiment was carried out, during the 1999 and 2000 growing season, at the Fundação Agrária de Pesquisa Agropecuária [Agrarian Foundation for Agricultural and Cattle Research] (FAPA), in Guarapuava, state of Paraná, Brazil, with the objective to verify the influence of the residual nitrogen fertilization on maize crop, on no tillage system, in presence and absence of white clover and grazing. The experimental design was the complete randomized blocks with tree replications. The treatments were arranged in split-plot model. During the previous Winter season four N levels (N-TI = 0, 100, 200 e 300 kg.ha-1 de N), were applied to the main plots, and the combination of presence and absence of white clover and grazing (CT = clover presence; ST = clover absence; CP = grazing presence, and SP = grazing absence), to the sub-plots. At the Summer season in each sub-plot prepared during the previous Winter season five N cover levels (N-TV = 0, 60, 120, 180 e 240 kg.ha-1 de N), were applied and corn cultivated. Eighteen days after the animals were removed out of the plots, the best technical re-growth efficiency of Winter plants was obtained with 231 kg.ha-1 de N (N-TI). The areas CP/N-TI showed tendency to present better corn production. The areas without N-TI yielded more in the SP subplots. The plots that received 300 kg.ha-1 de N N-TV did not show corn response to the N-TV, confirming the residual effect of N-TI. The conclusion is that the interaction between grazing and N-TI contributes to the maize nitrogen.